Two poems: The Singing Bowl; The Cannibal Doctors - Simpson, Anne; Blacquiere, Dylan (DALHOUSIE MEDICAL JOURNAL, 2005)
The Singing Bowl by Anne Simpson The Cannibal Doctors by Dylan Blacquiere (for Meredith)